Studi Eksperimen Virtual Konseling untuk Layanan Konseling Kelompok Bersama Mahasiswa Program Studi BKPI Di IAI BBC Tahun Ajaran 2018/2019 - Nakhma’ussolikhah, Nakhma’ussolikhah (Universitas Islam Bunga Bangsa Cirebon, 2020)
Virtual counseling is part of counseling through the internet in general referring to professions related to services through internet communication technology. Specifically, virtual counseling utilizes a variety of other online media that can be used to organize online counseling, such as social networks such as Facebook, Twitter, My Space, Email, WhatsApp, IG (Instagram) and several application programs for chatting (instant messaging) such as Skype, Messenger , google talk, window live messenger, even the use of telephones and mobile phones and special media teleconferences. Group counseling service is a process that occurs in group relationships with groups of people who experience problems but cannot be overcome, a professional expert who has gained training and experience to help the client / counselee is able to solve the problem being faced. This research was conducted to determine the experimental study of virtual counseling realization for group counseling services, how counselors in providing counseling services through internet technology can be used based on techniques, service strategies and methods of using appropriate services. As for BKPI students, they are the primary subjects, because seeing the phenomenon experienced by students is quite socially problematic so there is need for internet-based services or group counseling. This research is an experimental qualitative research which is a type of field research. After describing the data then comparing the opinions of both primary data sources and secondary data. This study departs from the problems experienced by first semester students as a transition period means the period in which individuals adapt back from high school to university level, in understanding the misuse of information technology that makes problems often experienced as a result of the internet. Through group counseling, students are expected to be able to utilize the use of technology as one of the processes to support services. The conclusions obtained from this study are: students who often use the website or the internet as a means of communication with lecturers turn out to have creative value when viewed from the perspective of guidance and counseling. Technology-based services make it a major need for students today to carry out the process of counseling on campus. With group counseling through technology, students begin to realize counseling. The nature of counseling services is personal, social, learning and career can be developed based on client needs. Keywords: Virtual Konseling; Group Counseling; Experiment Abstrak Virtual konseling merupakan bagian dari konseling melalui internet secara umum merujuk pada profesi yang berkaitan dengan layanan melalui teknologi komunikasi internet. Secara khusus virtual konseling memanfaatkan berbagai media online lain yang bisa digunakan untuk penyelenggaraan konseling online, seperti jejaring sosial misalnya facebook ,twitter, my space, email, whattsup, IG (Instagram) dan beberapa program aplikasi untuk chatting (instant messaging) seperti skype, messenger, google talk, window live messenger, bahkan penggunaan telepon dan handphone serta media khusus teleconference. Layanan konseling kelompok adalah suatu proses yang terjadi dalam hubungan kelompok dengan kelompok orang yang mengalami masalah namun tidak dapat diatasi, seorang ahli profesional yang telah memperoleh latihan dan pengalaman untuk membantu agar klien/ konseli mampu menyelesaikan permasalahan yang sedang dihadapi. Penelitian ini dilakukan untuk mengetahui studi eksperimen realisasi virtual konseling untuk layanan konseling kelompok, bagaimana konselor dalam pemberian layanan konseling melalui teknologi internet dapat digunakan berdasarkan teknik, strategi layanan dan metode penggunaan layanan yang tepat. Adapun mahasiswa BKPI, menjadi subjek primer, sebab melihat fenomena yang dialami mahasiswa cukup bermasalah secara sosial sehingga perlu adanya layanan berbasis internet atau konseling kelompok. Penelitian ini bersifat kualitatif eksperimen yang jenisnya adalah penelitian lapangan (Field research). Setelah memaparkan data kemudian membandingkan antara pendapat keduanya yaitu sumber data primer dan data sekunder.Penelitian ini berangkat dari permasalahann yang dialami mahasiswa semester pertama sebagai masa transisi artinya masa dimana individu beradaptasi kembali dari jenjang SMA ke PT, dalam memahami kekeliruan pemanfaatan teknologi informasi yang membuat permasalahan sering dialami akibat dari internet. Melalui konseling kelompok, mahasiswa diharapkan mampu memanfaatkan kegunaan teknologi sebagai salah satu proses penunjang layanan. Kesimpulan yang didapat dari penelitian ini adalah mahasiswa yang sering menggunakan website atau internet sebagai sarana komunikasi dengan dosen ternyata memiliki nilai kreatif ketika dipandang dari perspektif bimbingan dan konseling. Layanan berbasis teknologi menjadikan kebutuhan utama bagi mahasiswa saat ini untuk melangsungkan proses konseling di kampus. Dengan adanya konseling kelompok melalui teknologi, maka mahasiswa mulai menyadari akan konseling. Adapun sifat dalam layanan konseling bersifat pribadi, sosial, belajar maupun karir dapat dikembangkan berdasarkan kebutuhan klien. Kata kunci: Virtual Konseling; Konseling Kelompok; Eksperimen